Esophageal atresia and tracheoesophageal fistula: Effect of pleural cover on anastomotic dehiscence - Money Gupta; J K Mahajan; Monika Bawa; KLN Rao (Wolters Kluwer Medknow Publications, 2011)
Background: A significant number of esophageal atresia and tracheoesophageal fistula patients have long gaps and a high propensity to leak. Anastomotic leak in esophageal atresia is associated with a significant morbidity and mortality. Aim : In a prospective randomized trial, we analyzed the risk factors leading to anastomotic dehiscence and studied the effect of pleural wrap as an additional vascular cover around the esophageal anastomosis. Materials and Methods: Forty patients were divided into two groups A and B randomly. In 20 patients of group A, pleural wrap was utilized for covering the anastomosis and in 20 patients of group B, no such wrap was utilized. Results: Both the groups were comparable regarding age, sex, weight, gap length, tension at anastomosis and the hospital stay. The overall leak rate was 25% (10/40) in both the groups. The leak rate was not significantly different in two groups whenever a gap length was less than 2 cm or more than 3 cm. However, for a gap length of 2-3 cm, the leak rate in group A was 18% (2/11) and in group B was 50% (4/8) (P = 0.05). Thirty percent (3/10) of patients, whose anastomosis was under tension, leaked in group A as compared to 75% (6/8) in group B patients (P = 0.001). Conclusions: Use of pleural wrap was associated with less anastomotic dehiscence in patients with moderate gap esophageal atresia (2-3 cm) especially when the anastomosis was under tension.